2021
DOI: 10.32598/bcn.2021.2067.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Eight Weeks of Resistance Exercises on Expression of Neurotrophins and Trk Receptors in Alzheimer Model Male Wistar Rats

Abstract: This study aims to evaluate the effects of eight weeks of resistance exercises on expression of neurotrophins and Trk receptors in Alzheimer model male Wistar rats. For this purpose, 32 mature male Wistar rats with mean weights of 230 to 280 g were chosen and divided into Alzheimer and Sham groups. Rats in the Sham group received normal saline while rats in the Alzheimer group received STZ via intraventricular injection. These rats were then divided into the following four subgroups: 1. Resting Sham, 2. Exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Testing the changes in the levels of hippocampal proliferation markers is a supposedly suitable way of testing the effects of different variables on cognitive impairment, namely, memory and its many subtypes. Ki-67 is a direct proliferation marker found to be markedly reduced in the hippocampal samples of cisplatin-treated animals [ 32 ] and, on the other hand, increased in those given an exercise regimen [ 33 ]. In this study, we were able to support both findings concurrently where the total number of positive Ki-67 cells was higher among the exercise group in comparison to the cisplatin group, supporting the effect of exercise in protecting the hippocampal neurogenesis from cisplatin's toxic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Testing the changes in the levels of hippocampal proliferation markers is a supposedly suitable way of testing the effects of different variables on cognitive impairment, namely, memory and its many subtypes. Ki-67 is a direct proliferation marker found to be markedly reduced in the hippocampal samples of cisplatin-treated animals [ 32 ] and, on the other hand, increased in those given an exercise regimen [ 33 ]. In this study, we were able to support both findings concurrently where the total number of positive Ki-67 cells was higher among the exercise group in comparison to the cisplatin group, supporting the effect of exercise in protecting the hippocampal neurogenesis from cisplatin's toxic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle plays a crucial role in the production and secretion of many cytokines such as brainderived neurotrophic factor (BDNF) and insulin-like growth factor-1 [14], which are involved in neuronal survival, synaptic development, angiogenesis, learning, and neural plasticity [62]. Higher levels of these peptides have been correlated with greater physical fitness and increased GMV [58], and more importantly, studies showed that resistance activities could stimulate the release of BDNF and evoke neuroplastic changes in frontal and hippocampal regions, which may further translate into cognitive improvements [63][64][65]. Therefore, cytokine-induced alterations in GMV may represent a mechanism through which muscular fitness influences cognition and mental status, yet further research is needed [66].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in animal models of AD have also shown the positive effects of RE on memory deficits and cognitive dysfunction (Table 1; Özbeyli et al, 2017;Liu et al, 2020;Pena et al, 2020;Jafarzadeh et al, 2021). Liu et al found that RE could improve cognitive function in AD mice by reducing amyloid load and tau pathology, and attenuating neuroinflammation.…”
Section: Effects Of Re On Cognitive Function and Memory In Admentioning
confidence: 99%
“…Özbeyli et al (2017) showed that the improvement in working memory provided by RE may occur via oxidative stress and the antioxidant system. Another study by Jafarzadeh et al (2021) used a model of intraventricular injection of streptozotocin (STZ) in rats and observed that RE improved learning and memory, together with an increase in the expression of neurotrophic factors and their respective receptors. Although by different mechanisms, these studies showed improvements in memory and cognitive deficits in AD experimental models, and corroborate the results from studies with MCI patients.…”
Section: Effects Of Re On Cognitive Function and Memory In Admentioning
confidence: 99%
See 1 more Smart Citation